TRANSFORMATION OF H.P. LOVECRAFT’S COLOUR OUT OF SPACE SHORT STORY INTO MOVIE - Wira Indah Ayu; Husni Thamrin; Kunkun K. Harnady; Iwan Dudy Gunawan (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
The Research Entitled "Transformation of H. P. Lovecraft Colour Out of Space Into Movie" is about ecranization study of short story into a movie Colour Out of Space. The objectives of the research is to find addition, reduction and changes of variations of the Colour Out of Space short story into a movie. The reason why the researcher chooses Colour Out of Spaces is because it has a unique story about the colour that never be seen by human's eye, the research find it interesting to see the ecranization thay happened between the short story and the movie, also there are still few researchers who raise ecranization in research. This research used descriptive qualitative, and ecranization theory by Pamusuk Eneste to analyzed the addition, reduction and changes of variations. The researcher found there are addition, reduction, and changes of variations in the transfotmation of Colour Out of Space short story into a movie. There are addition, reduction, and changes of variations in plot and character. There are addition and reduction only for setting. The research then found all of the addition, reduction and changes of variations influenced some changes in the intrinsic elements in the transformation.